2013
DOI: 10.5657/fas.2013.0187
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the Sub-lethal Toxicity of Metals and Endocrine-disrupting Chemicals to the Marine Green Microalga Tetraselmis suecica

Abstract: Microalgae are sensitive indicators of environmental changes, and hence they are widely used in environmental risk assessments and for the development of discharge guidelines. Here we evaluated the toxicity of metals and endocrine-disrupting chemicals (EDCs) to the marine green microalga, Tetraselmis suecica. The toxicants investigated included the metals, Cu, Ni, and Pb; and the EDCs, bisphenol A (BPA), endosulfan (ES), and polychlorinated biphenyl (PCB). The endpoints were variations in cell counts and chlor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 26 publications
1
3
1
Order By: Relevance
“…Likewise, exposure of Cu resulted in marked reductions in Chl a concentration in the dinoflagellate Cochlodinium polykrikoides, an effect that was also more pronounced at higher Cu concentrations (Ebenezer et al 2014). Overall, these results clearly demonstrate that the Korean strain of C. ehrenbergii used in this study is considerably more sensitive to Cu than other microalgae that have been tested previously (Cairns et al 1978, Viana and Rocha 2005, Ebenezer and Ki 2013.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…Likewise, exposure of Cu resulted in marked reductions in Chl a concentration in the dinoflagellate Cochlodinium polykrikoides, an effect that was also more pronounced at higher Cu concentrations (Ebenezer et al 2014). Overall, these results clearly demonstrate that the Korean strain of C. ehrenbergii used in this study is considerably more sensitive to Cu than other microalgae that have been tested previously (Cairns et al 1978, Viana and Rocha 2005, Ebenezer and Ki 2013.…”
Section: Resultssupporting
confidence: 71%
“…1B). Previous studies have reported that EC 50 for the green algae Chlorella ellipsoidea, Chlorella vulgaris, Chlamydomonas sp., and Tetraselmis suecica were 0.489, 0.200, 8.00, and 43.03 mg L -1 , respectively (Young and Lisk 1972, Cairns et al 1978, Ebenezer and Ki 2013 The cultures were then re-suspended in fresh C medium, and mounted onto a slide and sealed; culture slides were observed with a fluorescence microscope (Carl Zeiss Axioskop, Oberkochen, Germany) to determine the level of ROS production in the cells. ImageJ software (NIH, Bethesda, MD, USA) was used to quantify relative CAF and ROS levels from the fluorescent microscopic images.…”
Section: Ros Measurementmentioning
confidence: 99%
“…has been reported to have a 72-h EC50 of 4.61 mg/L (Yamagishi et al 2016; shake flask test, 23 °C at ~4000 lux), 1 order of magnitude higher than our EC50s, which ranged from 0.66 to 64.5 mg/L. It has been suggested, however, that marine algae are more tolerant to some toxicants, notably metals, than freshwater species (Ebenezer and Ki 2013;Yamagishi et al 2016).…”
Section: Reference Toxicity Testingcontrasting
confidence: 75%
“…The EC 50 (96 h) of BPA for the freshwater algae (Chlorella pyrenoidosa and Scenedesmus obliquus) were 44.9 mg L −1 and 33.9 mg L −1 , respectively (Li et al 2017). Although previous findings suggest that the marine algae genus Tetraselmis is more tolerant to toxic chemicals than other algae (Ebenezer and Ki 2013), V2 strain seems to be the most sensitive to BPA. This study leads to suggest that our specie may be relatively more efficient in metabolites toxicity assessment due to its high sensitivity.…”
Section: Determination Of the Median Effective Concentration Of Bpa Amentioning
confidence: 83%